HUBUNGAN ANTARA INSENTIF DENGANMOTIVASI KERJA APARAT PEMERINTAH DESA DI KECAMATAN KAUDITAN KABUPATEN MINASAHA UTARA - PALALU, SUKRIANTO RAHMAT; DENGO, SALMIN; PLANGITEN, NOVVA (Sam Ratulangi University, 2018)
The purpose of this research was to determine the relationship of incentives to the motivation of work of village government officials in Kauditan District, North Minahasa Regency. This study uses quantitative methods. The research respondents were 30 village government officials in the Kauditan District taken in four villages. The instruments and data collection techniques used were questionnaires and assisted with interview quides. The analysis technique used for hypothesis testing is simple statistical analysis of correlation or product moment choreography. Based on the results of the data analysis, it was concluded that the incentives correlated or correlated significantly with the work motivation of village government officials; it means that the level of motivation of the work of the village government apparatus is significantly dependent on the incentives obtained as village government officials; the higher / better and satisfying incentives obtained by village officials, the higher or higher the motivation of work in carrying out their duties as a tool of the village government. Based on the results of this study, it can be recommended that incentives for village government officials need to be increased by increasing the amount of Village Fund Allocation each year. District governments also should allocate budgets for incentives for village government apparatus other than ADDKeywords:Incentives, Work Motivation, village Government Apparatus.